2012
DOI: 10.3109/10428194.2012.739285
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine can severely impair T-cell immunity against cytomegalovirus

Abstract: Bendamustine has rapidly become one of the key drugs for patients with indolent lymphoma because of its safety, tolerability and eff ectiveness. However, two of the 11 patients we have administered the drug developed severe immunosuppression against cytomegalovirus (CMV). Bendamustine potentially hampers immune function and should be used more cautiously.Case 1 A 51-year-old man was diagnosed with follicular lymphoma with massive bone marrow infi ltration in 2006. He received R-CHOP (rituximab, cyclophosphamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 4 publications
0
26
1
Order By: Relevance
“…Although studies have shown the risk of severe infection following treatment with bendamustine to be relatively low compared with that of conventional chemotherapeutic regimens [6], opportunistic infections, including cytomegalovirus reactivation, have been reported in some studies [7][8][9]. The rate of development of CMV reactivation was at least 20 % in the present study, as we did not measure this finding for every patient.…”
contrasting
confidence: 68%
“…Although studies have shown the risk of severe infection following treatment with bendamustine to be relatively low compared with that of conventional chemotherapeutic regimens [6], opportunistic infections, including cytomegalovirus reactivation, have been reported in some studies [7][8][9]. The rate of development of CMV reactivation was at least 20 % in the present study, as we did not measure this finding for every patient.…”
contrasting
confidence: 68%
“…These studies strongly suggest that an impaired T‐cell immunity function, determined by Alemtuzumab, may represent a high risk factor for CMV infection/reactivation and that patients treated with this drug should be prospectively and carefully monitored. Furthermore, a large amount of clinical cases of life‐threatening CMV reactivation in hematologic malignancies as well as limited single‐centre experiences have been reported in the last few years, all suggesting a possible role of previous treatment with Rituximab, Bendamustine, and Bortezomib as predisposing factors for CMV infection/reactivation . Unfortunately, due to the heterogeneity of these data, gathered from a variety of different clinical settings, it is difficult to identify other concomitant risk factors for CMV reactivation with some reliability.…”
Section: Cytomegalovirus Infection In Nontransplanted Patientsmentioning
confidence: 99%
“…Some studies found no increase of atypical infections, 7,8,17,18 whereas others noted conflicting data, 16,19 particularly with regard to cytomegalovirus infections. 19 …”
Section: Discussionmentioning
confidence: 97%
“…7,8,1619 Specifically, a significant decrease in CD4+ and CD8+ T-lymphocyte counts was observed for up to six months after the end of BR therapy although the impact of lymphopenia on the rate of infections has been controversial. Some studies found no increase of atypical infections, 7,8,17,18 whereas others noted conflicting data, 16,19 particularly with regard to cytomegalovirus infections. 19 …”
Section: Discussionmentioning
confidence: 99%